Use of pharmacogenomics in pediatric renal transplant recipients - Medeiros, Mara; Castañeda-Hernández, Gilberto; Ross, Colin J. D.; Carleton, Bruce C. (Frontiers in Genetics, 2015)
Pharmacogenomics in pediatric renal transplant